Оптимізація конструкції шнекового пресу шляхом чергування зон стиску і перемішування маси в шнековому тракті - Бровко, Руслан Сергійович; Пугач, Андрій Миколайович; Brovko, Ruslan; Puhach, Andrii (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті розглянуто питання оптимізації конструкції шнекового пресу шляхом чергування зон стиску та перемішування маси у шнековому тракті. Проведено аналіз існуючих конструкцій та встановлено вплив геометричних параметрів шнека на ефективність процесу пресування. Обґрунтовано доцільність функціонального зонування тракту, що забезпечує стабілізацію технологічного процесу, покращення перемішування сировини та рівномірний розподіл навантаження. Розроблено і запропоновано конструкцію шнекового пресу та шнекового тракту, яка включає 14-секційний вал із чотирма модифікованими дросельними втулками з зубчастим профілем. Впровадження цього рішення забезпечує ефективне перемішування та ущільнення матеріалу, рівномірний розподіл навантаження, підвищує продуктивність і стабільність роботи обладнання, знижує енергоспоживання та підвищує зносостійкість робочих органів. Встановлено, що застосування запропонованої конструкції дозволяє збільшити строк служби деталей у 1,5–2 рази, знизити енергоспоживання до 10 % та підвищити вихід олії на 5 %. /// EN: The article addresses the optimization of the screw press design through the alternation of compression and mixing zones in the screw channel. An analysis of existing designs showed that traditional solutions mainly focus on material compaction by reducing the screw pitch or changing the thread diameter, while insufficient attention is paid to intensifying mixing and equalizing the physico-mechanical properties of the material, which leads to uneven loading, local overloads, and reduced pressing efficiency. The study examined the influence of screw geometric parameters (pitch, diameter, thread height, surface profile) on material flow, compaction degree, and intensity of internal shear deformations. The feasibility of functional zoning of the screw channel was justified, where alternating compression and mixing zones stabilize the technological process, break agglomerates, equalize moisture, temperature, and structural properties, and prevent abrupt pressure gradients and channel blockage. A screw press and screw channel design has been developed and proposed, featuring a 14-section shaft with four modified throttle sleeves with a toothed profile, providing staged influence on the material, increasing productivity, improving material transport, reducing energy consumption, and enhancing wear resistance of working elements. It was found that the proposed solutions increase component service life by 1.5–2 times, reduce energy consumption by 10 %, and increase oil yield by approximately 5 %. The results confirm the effectiveness and feasibility of implementing these improvements and their positive impact on the technical and economic performance of the screw press.
Optimization of the screw press design by alternating compression and mixing zones in the screw channel
Keywords: олійний прес; шнековий тракт; модифікована конструкція; дросельні кільця; ефективність пресування; зносостійкість деталей; oil press; screw channel; modified design; throttle rings; pressing efficiency; wear resistance of parts